Lesson Planning in EFL Classroom: A Case Study in Lesson Plan Preparation and Implementation - Raynesa Noor Emiliasari (Universitas Wiralodra, 2019)
Lesson planning is an important stage that must be done by the teacher before teaching. Through careful planning, the learning process will be more organized. However, based on preliminary studies, it is known that teachers still have difficulties in preparing learning. Even though the learning has been prepared, the learning process goes beyond the plan. This study aims to: 1) explore the teachers’ preparation of teaching English; and 2) investigate the implementation of teachers’ lesson plan in teaching English. As a case study, the research site was in three of secondary schools in Majalengka. Three English teachers were involved as respondents. Interview, observation, and documentation were used to collect the data. The findings showed that teachers prepared the lesson plan by: 1) reviewing the core compentence and basic competence from the syllabus; 2) searching for learning resources; 3) choosing learning media; 4) determining the material; 5) selecting learning method; 6) compiling indicators and goals. However, the activities compiled in the lesson plan were not all implemented. Some disorders occured during the learning process because of teachers behalf, such as meeting, teachers profesionalism training, and other schools’ activities. If some learning activities did not implemented, the teachers made transactional decision to make up the class. Keywords : Lesson Planning, Teaching English, Preparation, Implementation.